Studies in asymmetric synthesis - Ravindran, Swarnam Shanthi (Rhodes University, Faculty of Science, Department of Chemistry, 1994)
The stereoselectivity of TiCI₄-catalysed Mukaiyama reactions of a camphor acetal-derived chiral silyl enol ether with a range of substituted aromatic aldehydes has been examined. The enantiomeric excess in each of the resulting ß-hydroxy ketones, determined by ¹H NMR spectroscopy using the lanthanide chiral shift reagent Pr(Etcf₃), ranged between 9 and 13%. The stereo-directing potential of the camphor acetal as a chiral auxiliary in the α-benzylation of carboxylate esters has been studied; the acids were chosen to illustrate substituent effects on asymmetric induction. The observed diastereoselectivity increased with increasing steric bulk of the ester group and α-benzylation of the tert-butylacetate derivative proceeded with 48% diastereoselectivity. It is proposed that the enolate adopts an endo-s-trans conformation in the transition state and preferential attack by the electrophile at the somewhat less hindered Si-face is supported by both the optical rotation data and computer modelling studies. Reductive cleavage and hydrolysis of one of the benzylated esters furnished known products from whose optical rotation the configuration of the major diastereomer was established. In order to improve the steric advantage of Si-facial attack, methods of increasing the steric bulk of the blocking group were explored. A novel 2,2-propylenedioxy hydroxycamphor acetal and its 3,3-propylenedioxy analogue were prepared. Selected carboxylate esters of these propylenedioxy acetals were subjected to α-benzylation and the 2,2-(propylenedioxy)-3-exo-tert-butylacetate derivative showed a diastereoselectivity of 57% during a-benzylation. Hydrolysis of the abenzylated phenylacetate analogue offered the known 2,3-diphenylpropanoic acid whose optical rotation indicated the preferred configuration at the new chiral centre to be (R), a result which is consistent with the proposed approach of the electrophile to the less hindered Re-face of theendo-s-trans enolate moiety and reflects an inversion of the configurational bias observed with 2-v exo-carboxylate analogues. Attempts to prepare the monocatechol acetal of the hydroxy camphor derivative although unsuccessful, led to the isolation of two novel dibornyl ethers whose structures were established by 1- and 2-D NMR spectroscopy. A study of novel applications of camphor-derived auxiliaries in the asymmetric synthesis of α-amino acids has been initiated. The several approaches tried led to the preparation of three novel dural glycine derivatives in good yield
Keywords: Asymmetric synthesis; Chirality; Organic compounds -- Synthesis